Men Who Have Sex with Men (MSM) Who Have Not Previously Tested for HIV: Results from the MSM Testing Initiative, United States (2012–2015) - Clark, Hollie A. (AIDS Behav, 2019)
The Centers for Disease Control and Prevention recommends annual HIV tests for men who have sex with men (MSM), yet some have never tested. We analyzed data from the MSM Testing Initiative. Of 68,185 HIV tests, 8% were with MSM who never previously tested (“first-time testers”). Among tests with first-time testers, 70.7% were with MSM from racial or ethnic minorities; 66.5% were with MSM younger than 30 years. Tests with MSM who reported female partners only during the past year (compared to male partners only) or were recruited for at-home testing (compared to venue-based recruitment) were 4 times (prevalence ratio [PR] 3.62, 95% CI 3.15–4.15) and 5 times as likely (PR 4.69, 95% CI 4.22–5.21) to be associated with first-time testing. At-home testing and focusing on MSM who have sex with women may be effective methods for reaching MSM who are first-time testers.